MAGNETIC PROPERTIES OF (Fe,Co)₅SiB₂ ALLOYS BY W DOPING - HIRIAN, Răzvan; POP, Viorel; ISNARD, Olivier; BENEA, Diana (Studia Universitatis Babeș-Bolyai Physica, 2022)
The intrinsic magnetic properties (magnetic moments, magneto-crystalline anisotropy, Curie temperatures) of the Fe5-x-yCoyWxSiB2 alloys have been calculated using the spin-polarized relativistic Korringa-Kohn-Rostoker (SPRKKR) band structure method. Our calculations show that for several compounds with x ≥0.5, the magnetocrystalline anisotropy energy (MAE) became axial. Also, theoretical calculations for Fe4WSiB2 compound found a magnetization decrease (with about 20%), a Curie temperature decrease of about 30% but an increased axial magnetocrystalline anisotropy compared with the corresponding values for Fe5SiB2. Several Fe5-xWxSiB2 alloys (x = 0, 0.1, 0.2, 0.5, 1) have been prepared by arc melting of corresponding high purity elements in Ar controlled atmosphere. Composition analysis of the Fe5-xWxSiB2 alloys found an impurity phase along with the tetragonal I4/mcm phase of pure Fe5SiB2. The magnetic measurements found the decrease of the magnetization any significant increase of the coercivity due to W doping.